'Tobacco Thrives, but the Environment Cries': The Sustainability of Livelihoods from Small-Scale Tobacco Growing in Zimbabwe, 2000–2017. (15th September 2019) - Nyambara, Pius; Nyandoro, Mark
This study analyses the environmental consequences of the introduction in 2000 of the volatile Fast Track Land Reform Programme (FTLRP) and the sustainability of livelihoods among small-scale African tobacco-farmers following the reform programme. Tobacco was significant in the colonial cash economy and remains a key cash crop in post-colonial Zimbabwe since 1980. Much of the extant tobacco literature focuses on white-settler tobacco farming in colonial and post-colonial Zimbabwe. This study adds to and builds upon an emerging scholarship on African small-scale tobacco producers. Some of the scholars studied the institutional history of tobacco growing and the associated tobacco research and others focused on marketing boards. Geist's work is particularly significant for this study because it examines the environmental impacts of tobacco growing in the developing world. This paper focuses on smallholder flue-cured tobacco growing in Zimbabwe. It observes that the post-independence government made concerted efforts to promote small-scale tobacco-farming through the land resettlement programme and the provision of incentives for increasing agricultural output as well as accelerated black farmers' involvement in the growing of commercial crops, notably tobacco and cotton. The study explores links between the FTLRP and the increase in smallholder tobacco growers and the resulting ecological and livelihood impacts. While tobacco and some tobacco growers appeared to thrive, the environment suffered. Using qualitative and quantitative research approaches and methods like interviews, direct observation, published secondary material, contemporary newspapers and Tobacco Industry and Marketing Board (TIMB) resources, the paper demonstrates that the FTLRP marked the drive to change livelihoods among Zimbabwean farmers.